The level of customer satisfaction towards service quality provided by IBFIM / Nur Izzatul Md.Shukri - Md.Shukri, Nur Izzatul (Faculty of Business and Management, 2008)
Training centre is an important place in providing training for the staffs. IBFIM has provided the training related to Islamic banking and finance for them who want to learn about Islamic banking industry. The purpose for this research is to study the customer's satisfaction towards the service quality provided by IBFIM. This study will examine the level of customer's satisfaction and the influence between service quality dimensions and customer satisfaction. Five dimensions in service quality which is consist of reliability, responsiveness, assurance, tangible and empathy play crucial to measure the level of customer satisfaction especially in lBFIM. Descriptive research has been adopted for this research. Questionnaires, interview and other secondary data including journals, internet and brochures are used for data - collection. 80 copies of questionnaires were distributed to the respondents who are attending courses at IBFIM. The sampling technique is convenience sampling. Descriptive statistics has been used to interpret the data to produce reliability test, frequency analysis, cross-tabulation analysis and regression analysis. Based on those statistics, a clear findings and result is observed. The findings showed that most of the customers are very satisfied with the service provided to them and service quality dimension seems to have influence with customer satisfaction. Recommendations and suggestion are put on how to improve and increase customer's satisfaction on the service provided by IBFIM.